RAPID AND SPESIFIC DETECTION OF MYCOBACTERIUM TUBERCULOSIS USING POLYMERASE CHAIN REACTION - Anita Kurniati; Desak Nyoman Surya Suameitra Dewi; Ni Nyoman Purwani (Journal of Vocational Health Studies)
Background: Tuberculosis (TB) is one of the major causes of health burden worldwide, especially in lower middle-income countries. TB is caused by Mycobacterium tuberculosis (MTB) and characterized by severe condition incuding coughing and fever. Purpose: To review the current methods for detection of TB using Polymerase Chain Reaction (PCR). Review: several studies have been done to give valuable insight into TB transmission, diagnosis, and treatment, however research  is constantly  needed  to decrease the incidence of eradicate TB. This infectious disease still give big health problem in all over the world by being second in causing high mortality rates after HIV/AIDS.  A specific, sensitive, rapid and cheap method for TB and other mycobacteria diagnosis in clinical specimen is a desperate needed in the laboratory diagnosis and hence management of tuberculosis. PCR as one of nucleic acid amplification assays have revolutionized MTB detection. Since it was first invented in fifteen years ago, it’s been through many developments. Conclusion: PCR  is one of the most specific and sensitive method currently available for TB diagnosis that can also detect in in all types of specimens obtained from TB patients.